2021
DOI: 10.1177/13678779211011635
|View full text |Cite
|
Sign up to set email alerts
|

A Brazilian Hollywood in the making? Film, tourism and creative city discourse in the hinterland of Paraíba

Abstract: Originating in metropoles in the Global North, the creative cities model has increasingly been replicated in locations around the globe. However, betting on the creative industries to reinvigorate stagnant economies might not be a solution compatible with every context. To analyse this issue, this article presents the case of the small Brazilian city of Cabaceiras, which was the target of a project aimed at revitalizing its economy through film and tourism in 2007. Based on 25 interviews with residents and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The vulnerabilities experienced by Alter do Chão make the village comparable to other sensitive locations targeted for cultural projects in Brazil. Previous research on filmrelated initiatives developed in such places demonstrated that these projects often bring only temporary benefits to the communities involved, failing to live up to their wishes and expectations (Póvoa et al, 2019(Póvoa et al, , 2021. Some of the reasons for this are the positioning of these locations outside the country's creative hubs in the Southeast region, which results in such initiatives being carried out by 'outsider' creative workers who only engage with communities for a short period of time, and the non-prioritization of local circumstances in the creation and execution of these projects (Póvoa et al, 2021).…”
Section: Festivals Communities and Power Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vulnerabilities experienced by Alter do Chão make the village comparable to other sensitive locations targeted for cultural projects in Brazil. Previous research on filmrelated initiatives developed in such places demonstrated that these projects often bring only temporary benefits to the communities involved, failing to live up to their wishes and expectations (Póvoa et al, 2019(Póvoa et al, , 2021. Some of the reasons for this are the positioning of these locations outside the country's creative hubs in the Southeast region, which results in such initiatives being carried out by 'outsider' creative workers who only engage with communities for a short period of time, and the non-prioritization of local circumstances in the creation and execution of these projects (Póvoa et al, 2021).…”
Section: Festivals Communities and Power Dynamicsmentioning
confidence: 99%
“…Previous research on filmrelated initiatives developed in such places demonstrated that these projects often bring only temporary benefits to the communities involved, failing to live up to their wishes and expectations (Póvoa et al, 2019(Póvoa et al, , 2021. Some of the reasons for this are the positioning of these locations outside the country's creative hubs in the Southeast region, which results in such initiatives being carried out by 'outsider' creative workers who only engage with communities for a short period of time, and the non-prioritization of local circumstances in the creation and execution of these projects (Póvoa et al, 2021). Even though the organizers of FestAlter seemed to avoid such pitfalls by proposing collaboration with the Alter do Chão community, they still faced local resistance and conflict, as expressed in the open letter against them.…”
Section: Festivals Communities and Power Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Europe is the source of Western culture and has a wealth of cultural heritage and resources. Meanwhile, Britain, Germany, France and other European countries have developed steadily in science, technology and economy and have a good foundation and potential for developing cultural and creative industries [4][5]. Under the big platform of the EU, how to coordinate the interests of each member state, give play to synergistic advantages and drive overall development is also a problem that the EU needs to face in the new period.…”
Section: Introductionmentioning
confidence: 99%